2003
DOI: 10.1099/vir.0.18839-0
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic subunit of protein kinase CK2 phosphorylates in vitro the movement protein of Tomato mosaic virus

Abstract: The movement protein (MP) of Tomato mosaic virus (ToMV) was reported previously by us to be phosphorylated in vitro by a cellular protein kinase(s) that exhibited several characteristics of casein kinase 2 (CK2). To characterize further this CK2-like cellular kinase, we have cloned cDNAs encoding the CK2 catalytic subunit from tobacco and compared the properties of the recombinant protein with those of the CK2-like cellular kinase. The recombinant CK2 catalytic subunit formed a complex with ToMV MP and phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…A plant protein kinase with the biochemical properties of CK2 (formerly casein kinase II) has been shown to interact specifically with the MP of Tomato mosaic virus , a virus closely related to TMV, and to phosphorylate it in vitro ( Matsushita et al, 2000). This result was confirmed recently using the recombinant ␣ -catalytic subunit of CK2 from tobacco (Matsushita et al, 2003).…”
Section: Introductionsupporting
confidence: 66%
“…A plant protein kinase with the biochemical properties of CK2 (formerly casein kinase II) has been shown to interact specifically with the MP of Tomato mosaic virus , a virus closely related to TMV, and to phosphorylate it in vitro ( Matsushita et al, 2000). This result was confirmed recently using the recombinant ␣ -catalytic subunit of CK2 from tobacco (Matsushita et al, 2003).…”
Section: Introductionsupporting
confidence: 66%
“…Unlike studies of PVX viral movement and replication, interactions between PVX and host proteins are not well described. Among such studies the protein kinase CK2 was found to phosphorylate PVX TGB1 (Modena et al, 2008), as also reported for Tomato mosaic virus (ToMV) P30 movement protein (Lee 2008; Matsushita et al, 2003). In addition, another host protein, remorin (REM) which is located in the cytosolic leaflet of plasma membrane microdomains (lipid rafts) and in clusters at plasmodesmata (Pd), interacts with TGB1 to transport PVX to Pd (Raffaele et al, 2009).…”
supporting
confidence: 55%
“…Plant cell kinases mediate viral protein phosphorylation (1–16). The functional implications of the phosphorylation of nonstructural viral proteins have been elaborated (1–4,8–10,14,17–33), and the kinases involved have been characterized to some extent (4,5,7,8,12,13,15,21,27,28,34,35). Cell-to-cell movement of viruses involves the formation of a ribonucleoprotein (RNP) complex that interacts with host protein(s) to increase the size exclusion limit of plasmodesmata and to potentiate its own transport into neighboring cells (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane association of TMV MP is eliminated by phosphorylation (24). In Tomato mosaic virus (ToMV) MP, Ser-28 and -37 are the preferable contexts for phosphorylation by casein kinase 2 (CK2), CK2-like protein kinase or recombinant N. tabacum RIO kinase (3,6,7,25). Ser-37 phosphorylation profoundly affects the cell-to-cell movement of the viral genome and the subcellular distribution of ToMV-MP (18).…”
Section: Introductionmentioning
confidence: 99%